Maternal perception of malnutrition among infants using verbal and pictorial methods in Kenya - Mwangome, M; Fegan, G; Prentice, A; Berkley, J (Cambridge University Press, 2014)
Objective: To compare mothers’ perceptions of their own infants’ nutritional status with anthropometric indicators of undernutrition. Design: A qualitative study and cross-sectional quantitative survey. The qualitative study involved developing tools to assess mother’s perception. Two methods of verbal description and a pictorial scale were developed. The quantitative survey involved measuring maternal perception and comparing it with the anthropometric measures of weight-for-age Z-score (WAZ) and mid-upper arm circumference-for-age Z-score (MUACZ). Setting: A rural community setting in Kenya. Subjects: Seventy-four infants aged between 4 and 6 months, and their mothers, living in rural Kenya were enrolled. Results: Using verbal description, the positive and negative likelihood ratios were 3·57 (95 % CI 1·44, 9·98) and 0·69 (95 % CI 0·50, 0·96) respectively for MUACZ<−2; and 4·60 (95 % CI 1·60, 13·3) and 0·67 (95 % CI 0·49, 0·92) respectively for WAZ<−2. Using the pictorial scale, the positive and negative likelihood ratios were 8·30 (95 % CI 1·91, 36·3) and 0·69 (95 % CI 0·52, 0·93) respectively for MUACZ<−2; and 4·31 (95 % CI 1·22, 15·0) and 0·78 (95 % CI 0·61, 1·00) respectively for WAZ<−2. Conclusions: In a rural community, mothers better identify undernutrition in their infants using a pictorial scale than verbal description. However, neither can replace formal anthropometric assessment. Objective anthropometric tools should be validated for identification of severe acute malnutrition among infants aged less than 6 months.